Design of Intermediate Medical Record Information System in Electricity Patient Using Rolap Warehouse Data - Pramita, Made Dinda Pradnya; Subiksa, Gde Brahupadhya; Saputra, Komang Oka (International Journal of Engineering and Emerging Technology; Vol 3 No 1 (2018): January - June, 2018)
Along with the development of information and communication technology (ICT), which has become a major influence for change in all sectors, including health, especially in medical records is called electronic medical record. Basically an electronic medical record is the use of electronic methods to collect, store, process, and access patient records in hospitals that have been stored in a multimedia database management system, bringing together various medical data sources. Often the problem arises there is no relationship between the respective health care providers in terms of information on the medical record. Although the patient may have a medical examination at a health care provider vary at a certain time. This leads to the same inspection occurring repeatedly. Whereas previous medical records are very useful in further medical examination. Of the several problems mentioned above have designed a centralized electronic medical record system that accommodates patient medical records in a centralized database for the purpose of patient records stored in a single database storage. So if one day the patient is registered in the system, if referred from one hospital to another hospital in the area, data can be viewed and accessed based on data from the hospital or health care provider who has joined in this system. With this system helps reduce the possibility of misdiagnosis. Keywords: Centralized Medical Record, Data Warehouse and ROLAP